TFEB-mediated Enhancement of the Autophagy-lysosomal Pathway Dually Modulates the Process of Amyloid β-Protein Generation in Neurons. (15th March 2019) - Yamamoto, Fumiko; Taniguchi, Kaori; Mamada, Naomi; Tamaoka, Akira; Kametani, Fuyuki; Lakshmana, Madepalli K.; Araki, Wataru
Highlights: TFEB enhanced ADAM10 protein levels, but did not affect those of APP, BACE1, or γ-secretase complex components. TFEB augmented β-CTF levels possibly through altered proteasome-mediated catabolism. TFEB decreased the amount of secreted Aβ under the basal condition, but increased it when APP or β-CTF was co-overexpressed. TFEB-mediated ALP enhancement appears to have dual, but opposite, effects on Aβ production in neurons. Abstract: Abnormalities of the autophagy-lysosomal pathway (ALP) have been implicated in the pathology of Alzheimer's disease (AD). Activation of TFEB (transcription factor EB), a master regulator of the ALP, leads to ALP facilitation. The present study sought to clarify whether TFEB-mediated ALP facilitation influences the process of amyloid β-protein (Aβ) generation in neurons. TFEB was overexpressed in mature rat primary cortical neurons via recombinant adenoviruses, without (basal conditions) or with co-overexpression of wild-type amyloid precursor protein (APP) or its β-C-terminal fragment (β-CTF). We confirmed that TFEB overexpression upregulated the lysosomal proteins, cathepsin D and LAMP-1. In TFEB-expressing neurons, protein levels of ADAM10 were profoundly increased, whereas those of APP, BACE1, or γ-secretase complex proteins were unaffected. However, TFEB did not affect ADAM10 mRNA levels. TFEB overexpression had different effects on Aβ production depending on the expression level of APP or β-CTF: TFEB slightly decreased Aβ secretion under basal conditions; clearly increased α-CTF levels and marginally increased β-CTF levels with modest increases in secreted Aβ in APP-expressing neurons; and caused a remarkable increase in β-CTF levels with a significant increase in secreted Aβ in β-CTF-expressing neurons. Inhibition of proteasomes, but not lysosomes, markedly increased β-CTF levels in β-CTF-expressing neurons. These results collectively indicate that TFEB modulates Aβ production not only by increasing α-secretase processing of APP through ADAM10 upregulation but also by augmenting β-CTF levels possibly via altered proteasome-mediated catabolism. Thus, TFEB-mediated ALP enhancement appears to have dual, but opposite, effects on Aβ production in neurons.